2002
DOI: 10.1119/1.1435347
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanics for everyone: Hands-on activities integrated with technology

Abstract: Frequently, quantum mechanics is taught toward the end of the first year of physics -if it is taught at all. The reason for delaying the study is that quantum mechanics is a very abstract idea without much practical purpose. Therefore, students cannot understand it until they have learned all the rest of physics. We are challenging that way of thinking by creating instructional materials for quantum mechanics that can be integrated throughout the first physics course rather than just tacked on at the end. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 14 publications
2
106
0
3
Order By: Relevance
“…They found that almost all students accurately conceptualized the quantum phenomena. Zollman and his colleagues 2 argued that quantum mechanics learning is not as difficult as it is commonly perceived. They suggested that non-science high school and first year college students have the capacity to comprehend quantum mechanics without classical mechanics backgrounds.…”
Section: Background and Motivationmentioning
confidence: 99%
“…They found that almost all students accurately conceptualized the quantum phenomena. Zollman and his colleagues 2 argued that quantum mechanics learning is not as difficult as it is commonly perceived. They suggested that non-science high school and first year college students have the capacity to comprehend quantum mechanics without classical mechanics backgrounds.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Therefore, the focus is often on conceptual understanding (see, for example, Refs. [5][6][7]). There have been several researchbased reforms that attempt to improve this type of instruction [5,6,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]). There have been several researchbased reforms that attempt to improve this type of instruction [5,6,[8][9][10][11][12]. Although students have the prerequisite knowledge for learning superposition at this level, there has been disagreement among faculty regarding its importance in a modern physics course [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several prior studies have found that many advanced students struggle with the foundational issues in quantum mechanics including measurement (e.g., see [1][2][3][4][5][6][7][8][9][10][11][12]). Studies have focused on diverse pedagogical approaches for helping students learn quantum mechanics better (e.g., see [13][14][15][16][17][18][19][20][21][22][23][24][25][26]), and visualization tools such as QuVIS and QuTIP have been developed to help students develop intuition about quantum mechanical phenomena [23,24].…”
Section: Introductionmentioning
confidence: 99%